A client-centric risk-based taxonomy of service triads. Issue 15 (10th December 2022) - Sengupta, Sourav; Niranjan, T. T.; Krishnamoorthy, Mohan; van der Valk, Wendy
ABSTRACT: In client-provider-customer service triads, direct interactions between the providers and customers result in clients' exposure to various risks. This paper develops a taxonomy of service triads based on four attributes of outsourced services that result in those risks: 1) business impact; 2) customer contact; 3) mode of interaction; and 4) relationship continuity. We conduct a qualitative study to develop a contextually rich understanding of the resulting taxonomy. Characterization of the four taxons, namely, 'low-hazard, ' 'easily-monitored, ' 'to-be-watched, ' and 'vulnerable' service triads, based on agency theory, contributes to the understanding of how these services have traits and risks that are different from one another. It also provides insights into how the providers in each of the four taxons should be contracted and managed.